The magnetic states in cobalt‑promoted MoS2 microspheres - Ramos Murillo, Manuel Antonio (2024)
The cobalt-promoted MoS2 microspheres have been synthesized by hydrothermal methods using sodium molybdate precursors. Scanning electron microscopy indicates that spherical shape morphology and cobalt atoms are detected at MoS2 edges corresponding to (101)-plane as revealed by Cs-corrected transmission electron microscopy. The magnetic states were measured by magnetization curves obtaining a 0.044 emu/g due to paramagnetic contribution. Furthermore, the electronic structure from the density of states for 2H-MoS2 with and without cobalt at the (101) edge plane possesses a magnetic property with a value of 0.16 μB attributed to broken symmetry.